Myocardial Redox Hormesis Protects the Heart of Female Mice in Sepsis. Issue 1 (July 2019) - Luptak, Ivan; Croteau, Dominique; Valentine, Catherine; Qin, Fuzhong; Siwik, Deborah A.; Remick, Daniel G.; Colucci, Wilson S.; Hobai, Ion A.
Abstract : ABSTRACT: Mice challenged with lipopolysaccharide develop cardiomyopathy in a sex and redox-dependent fashion. Here we extended these studies to the cecal ligation and puncture (CLP) model. We compared male and female FVB mice (wild type, WT) and transgenic littermates overexpressing myocardial catalase ( CAT ). CLP induced 100% mortality within 4 days, with similar mortality rates in male and female WT and CAT mice. 24 h after CLP, isolated (Langendorff) perfused hearts showed depressed contractility in WT male mice, but not in male CAT or female WT and CAT mice. In WT male mice, CLP induced a depression of cardiomyocyte sarcomere shortening (ΔSS) and calcium transients (ΔCai ), and the inhibition of the sarcoplasmic reticulum Ca 2+ ATPase (SERCA). These deficits were associated with overexpression of NADPH-dependent oxidase (NOX)-1, NOX-2, and cyclooxygenase 2 (COX-2), and were partially prevented in male CAT mice. Female WT mice showed unchanged ΔSS, ΔCai, and SERCA function after CLP. At baseline, female WT mice showed partially depressed ΔSS, ΔCai, and SERCA function, as compared with male WT mice, which were associated with NOX-1 overexpression and were prevented in CAT female mice. In conclusion, in male WT mice, septic shock induces myocardial NOX-1, NOX-2, and COX-2, and redox-dependent dysregulation of myocardial Ca 2+ transporters. Female WT mice are resistant to CLP-induced cardiomyopathy, despite increased NOX-1 and COX-2 expression, suggesting increased antioxidant capacity. Female resistance occurred in association with NOX-1 overexpression and signs of increased oxidative signaling at baseline, indicating the presence of a protective myocardial redox hormesis mechanism. Abstract : Supplemental Digital Content is available in the text